Childhood cancer in Africa. Issue 4 (8th November 2013) - Kruger, Mariana; Hendricks, Marc; Davidson, Alan; Stefan, Cristina D; van Eyssen, Ann L; Uys, Ronelle; van Zyl, Anel; Hesseling, Peter
<x xml:space="preserve">Abstract</x> The majority of children with cancer live in low‐ and middle‐income countries (LMICs) with little or no access to cancer treatment. The purpose of the paper is to describe the current status of childhood cancer treatment in Africa, as documented in publications, dedicated websites and information collected through surveys. Successful twinning programmes, like those in Malawi and Cameroon, as well as the collaborative clinical trial approach of the Franco‐African Childhood Cancer Group (GFAOP), provide good models for childhood cancer treatment. The overview will hopefully influence health‐care policies to facilitate access to cancer care for all children in Africa. Pediatr Blood Cancer 2014;61:587–592. © 2013 Wiley Periodicals, Inc.